MEMBANGUN BURSA EFEK SYARIâAH YANG BERKUALITAS DAN BERDAYA SAING TINGGI - Irfan Shofwani, Muhammad (Al-Mawarid Jurnal Hukum Islam, 2003)
Stock Exchange Market is one of effective tool to accelerate the development of the country. Stock Exchange Market is one of alternative that can be used by the company to get capital needs. Althoght it has been banking institution, cause of leverage case, the company cannot get the many from bank instituion. Stock exchange market and bank institution have to be good partner. Economic crisis in 1997 had been a moment that realize Indonesian toward the weakness of economic macro and micro. The great of Indonesia development result in New Order era with Gross Domestic Bruto (GDP) and Gross National Bruto (GNP) indicator was only be deceit power. One of reasons was that our national power bulit on abroad debt, even government or non-government. The situation caused many dificulties when many of investation capital brought out of the country. The market need reformation, need not intervention. This is one of the opprotunies for academist and economist for developing moneter institution based on Syariâah values. The proof of Bank Muamalat Indonesia (BMI) ability to exist in our banking system, when many others colaps, can be capital to develop Syariâah economic institutions. Although the total asset of Syariâah banking only 0,23% of nasional banking asset, but the development shows great signs. As a part of national moneter system, Syariâah banking needs to be sopported by Islamic Exchange Market